Anticoagulation after Spontaneous Intraparenchymal Hemorrhage in Patients with Mechanical Heart Valves and Concomitant Atrial Fibrillation - Jennifer H. Kang (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Aim Patients with mechanical heart valves and coexisting atrial fibrillation (AFib-MHV) who suffer an intraparenchymal hemorrhage (IPH, defined as bleeding solely within the brain parenchyma and/or ventricle) are at a high risk of thromboembolism without anticoagulation. Data are lacking regarding the safety of early re-initiation of anticoagulation in these patients. Patients and Methods We performed a descriptive, single-institution retrospective analysis of patients with AFib-MHV who suffered a non-traumatic, supratentorial IPH between July 2013 and June 2017. We analyzed the patients and IPH characteristics, anticoagulation and antiplatelet use, the occurrence of thrombotic and hemorrhage complications, and discharge disposition. We described the timing of initiation of anticoagulation and outcomes after IPH while in-patient. Results Six patients with AFib-MHV suffered a spontaneous IPH. Four were initiated on anticoagulation prior to discharge, of whom two were initiated within 3 days post-hemorrhage. These patients suffered no bleeding complications and were discharged home with a modified Rankin Scale of 1. Conclusion Patients with AFib-MHV who suffer a spontaneous IPH are a rare population to study. Further studies to guide the management of restarting anticoagulation in this select population are warranted.